Aplikasi Web Pencarian Barang Hilang dengan Deteksi Lokasi Berbasis Google Map API - Chandra, Iwan; Irawati, Esther; Archie Kosasih, Richard (Fakultas Teknik dan Teknologi - TANRI ABENG UNIVERSITY, 2023)
Technological developments have developed rapidly, where people can share information quickly and efficiently. This research made some observations about utilizing website system technology to search for lost items that inform the point of finding the location of the goods, so that the finder of the goods can inform their discovery through the website. The website system supports the google maps API, claims of goods, and information about information on finding goods. This application development uses React.js javascript to build a more sophisticated and easy-to-use interface for application users.